Melding police and policy to dramatically reduce crime in the city of New Orleans: a study of the New Orleans Police Department - Unter, Kevin A. (Edwin Mellen Press)
A history of crime in New Orleans and the impetus for change -- The public policy approach to crime reduction -- Policing and crime reduction - in general and in New Orleans -- Establishment of models and tests of hypotheses of crime reduction -- Judging crime policy effectiveness